Frailty among hemodialysis patients - Adi, Ginanjar Sasmito; Utomo, Eri Purba (MEDISAINS, 2022)
Introduction: Hemodialysis patients have physical vulnerability due to the progressive decline of the body's systems. The physical changes in the patients can lead to haemostatics failure, known as frailty syndrome. The frail condition can cause maladaptive psychological responses due to changes that can cause anxiety in patients.Objective: This study aims to determine the prevalence of frailty in hemodialysis patients and to find out the different factor that correlates in frailty patients undergoing hemodialysis therapy.Method: This is a cross-sectional study involving 55 respondents who underwent hemodialysis therapy at the Jember Klinik Hospital. The instruments used in this study were the Edmonton Frail Scale (EFS) and the Hamilton Anxiety Rating Scale. Results: Moderate frailty was found in 23 patients (41.8%), followed by mild frailty in 18 patients (32.7%) and severe frailty in 14 patients (25.5%). In terms of anxiety, 18 patients (32.7%) had severe anxiety, 20 had moderate anxiety (36.4%), 12 (21.8%) had mild anxiety, and the other 7 (12.7%) were not anxious. The statistical analysis shows a significant difference in the average level of anxiety and the frailty status (p<0.001) among the patients. Conclusion: Frailty was highly prevalent in hemodialysis patients and had relations with anxiety and different sociodemographic characteristics of patients. The assessment of frailty should be considered when clinicians intervene and prevent worsening in patients.